Effects of precision demands and mental pressure on muscle activation and hand forces in computer mouse tasks. - Visser B; De Looze MP; De Graaff MP; Van Dieén JH (Ergonomics, 2004)
The objective of the present study was to gain insight into the effects of precision demands and mental pressure on the load of the upper extremity. Two computer mouse tasks were used: an aiming and a tracking task. Upper extremity loading was operationalized as the myo-electric activity of the wrist flexor and extensor and of the trapezius descendens muscles and the applied grip- and click-forces on the computer mouse. Performance measures, reflecting the accuracy in both tasks and the clicking rate in the aiming task, indicated that the levels of the independent variables resulted in distinguishable levels of accuracy and work pace. Precision demands had a small effect on upper extremity loading with a significant increase in the EMG-amplitudes (21%) of the wrist flexors during the aiming tasks. Precision had large effects on performance. Mental pressure had substantial effects on EMG-amplitudes with an increase of 22% in the trapezius when tracking and increases of 41% in the trapezius and 45% and 140% in the wrist extensors and flexors, respectively, when aiming. During aiming, grip- and click-forces increased by 51% and 40% respectively. Mental pressure had small effects on accuracy but large effects on tempo during aiming. Precision demands and mental pressure in aiming and tracking tasks with a computer mouse were found to coincide with increased muscle activity in some upper extremity muscles and increased force exertion on the computer mouse. Mental pressure caused significant effects on these parameters more often than precision demands. Precision and mental pressure were found to have effects on performance, with precision effects being significant for all performance measures studied and mental pressure effects for some of them. The results of this study suggest that precision demands and mental pressure increase upper extremity load, with mental pressure effects being larger than precision effects. The possible role of precision demands as an indirect mental stressor in working conditions is discussed.